L’agglomération de Chilleurs-aux-Bois (Loiret) durant l’Antiquité tardive - Laurent Fournier; Thomas Guillemard (Gallia)
Chilleurs-aux-Bois has experienced, between 2006 and 2013, six preventive archaeology investigations, widely contributing to improve our knowledge of this antique agglomeration situated along the road from Orleans to Reims. Late Antiquity is one of the periods which are best represented on each of these operations thanks to which the occupation of this small town between the second half of the 3rd c. and the beginning of the 6th c. AD. can be assessed.